Etika Berkomunikasi Di Media Sosial Dalam Mensikapi Informasi Penyebaran Covid 19 Di Lamongan: Studi Etnografi Virtual Di Media Sosial Instagram Pada Akun dinkes_kablamongan - Mubarok Ahmadi; Tri Tami Gunarti (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2021)
The development of information technology makes it easier to obtain and disseminate information, information is mushrooming so that the quality of information is questioned. Various hoax information is mushrooming among the public so it is confusing in responding to it so that communication ethics must exist. With one of the social media platforms, Instagram, information can be conveyed quickly and an Instagram profile is conveyed correctly so that people who receive information can be precise. This study uses a virtual ethnographic study by making observations on the Instagram account of the Health Office_kablamongan. This research results in information that can be published optimally through Instagram, provided that the identity of an Instagram account is written clearly.